This is assisted dying : a doctor's story of empowering patients at the end of life - Green, Stefanie (Scribner, 2022)
"Dr. Stefanie Green has been forging new paths in the field of medical assistance in dying since 2016. In her landmark memoir, Dr. Green reveals the reasons a patient might seek an assisted death, how the process works, what the event itself can look like, the reactions of those involved, and what it feels like to oversee proceedings and administer medications that hasten death. She describes the extraordinary people she meets and the unusual circumstances she encounters as she navigates the intricacy, intensity, and utter humanity of these powerful interactions. Deeply authentic and powerfully emotional, This Is Assisted Dying contextualizes the myriad personal, professional, and practical issues surrounding assisted dying by bringing readers into the room with Dr. Green, sharing the voices of her patients, her colleagues, and her own narrative. As our population confronts issues of wellness, integrity, agency and community, and how to live a connected, meaningful life, this progressive and compassionate book by a physician at the forefront of medically assisted dying offers comfort and potential relief. This Is Assisted Dying will change the way people think about their choices at the end of life, and show that assisted dying is less about death than about how we wish to live."--Publisher's website.